The antecedents of automobile brand loyalty: evidence from Malaysian - Mabkhot, Hashed Ahmad; Md Salleh, Salniza; Shaari, Hasnizam (2016)
This study empirically examined the mediating effect of brand satisfaction on the relationship between brand image and brand loyalty among Malaysian customer toward local automobile brands. Four hypotheses were developed to test hypothesizing relationships among brand image, brand satisfaction on brand loyalty.Data collected from customers of automobile brands in north Malaysia peninsula from three states which were Kedah, Penang, and Perlis.This study applies partial least squares to a sample of 458 customers to test hypothesized relationships. The findings indicate that brand image and brand satisfaction appear to have significant and positive relationship with brand loyalty.Brand satisfaction mediates the relationship between brand image and brand loyalty.The results are compared with earlier findings and implications for further research are discussed.